FAKTOR PENENTU PRODUKSI IKAN KERING DI KABUPATEN MUKOMUKO, BENGKULU, INDONESIA - Agung Trisusilo; Heni Anisa; Gita Mulyasari (Musamus Journal of Agribusiness, 2022)
Dried fish producers at Mukomuko Regency manage their business traditionally and rally on individual skills. Furthermore, the sustainability of this business is also very reliant on the availability of capital from each one of them. Therefore this research aims to analyze the determining factors of dried fish production in Mukomuko Regency, Bengkulu Province. The study conducted in Mukomuko Province involves 67 dry fish producers as respondents. This study used descriptive quantitative method and multiple linear regression analysis with ordinary least square (OLS) method. The research results show that the value of R2 is 0,8773. The results of the F-test show that the raw materials, labor, and capital are affected to the production of dried fish simultaneously. The T-test result indicated that the production of dried fish is subject to independent variables intermediates.